2021
DOI: 10.1055/a-1704-1851
|View full text |Cite
|
Sign up to set email alerts
|

Blood Pressure Goals: Is Cerebral Saturation the New Mean Arterial Pressure?

Abstract: Objective: To correlate hypotension and cerebral saturation from near-infrared spectroscopy (cNIRS) in neonates on dopamine. Study Design: Retrospective review of neonates receiving dopamine between August 2018-2019 was performed. Hypotension thresholds included mean arterial pressure (MAP) of postmenstrual age (PMA) ± 5mmHg, 30mmHg, and gestational age (GA) ± 5mmHg. Time below threshold MAP was compared to time with cerebral hypoxia (cNIRS <55%). Results: Hypotension occurred 6-33% of time on dopamine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…The important differences and limitations of the published study design, along with the complex pathophysiology of AH in preterm infants, add to the difficulties in defining and treating AH in this fragile population [7,20,26]. In fact, a prospective observational study showed that 3-49% of ELBWI with low AP did not receive anti-hypotensive treatment; however, 28-41% of infants without low AP were treated.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The important differences and limitations of the published study design, along with the complex pathophysiology of AH in preterm infants, add to the difficulties in defining and treating AH in this fragile population [7,20,26]. In fact, a prospective observational study showed that 3-49% of ELBWI with low AP did not receive anti-hypotensive treatment; however, 28-41% of infants without low AP were treated.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the use of targeted neonatal echocardiography and Near-InfraRed Spectroscopy (NIRS) monitoring for assessing heart function and cerebral perfusion, respectively, can add to the identification of AH needing inotrope/vasopressor treatment. The importance of NIRS as a complementary tool for the evaluation of the hypotensive neonate is supported by studies showing that cerebral oxygen delivery may not correlate with the presence of hypotension [20,25]. This finding suggests that the low AP measurement cannot accurately indicate potentially decreased cerebral oxygenation, which is a central target of anti-hypotensive treatment [20,[25][26][27].…”
Section: Definitions Of Arterial Hypotension In Neonatesmentioning
confidence: 99%
See 3 more Smart Citations